The Relationship Between Nationalism and Per Capita Gross National Product: Comment - Silver, Morris (Quarterly Journal of Economics, 1967)
Journal Article The Relationship Between Nationalism and Per Capita Gross National Product: Comment Get access Morris Silver Morris Silver City College of New York Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 81, Issue 1, February 1967, Pages 155–157, https://doi.org/10.2307/1879679 Published: 01 February 1967